Integrative Analysis of the Pharmacological Activities of Lumbricus rubellus: Evidence from Preclinical and Clinical Research - Iyan Hardiana; Elly Wahyudin; Muhammad Aswad; Rina Agustina (Borneo Journal of Pharmacy, 2025)
Lumbricus rubellus, commonly known as the red earthworm, has long been used in traditional medicine and contains diverse bioactive compounds with therapeutic potential. However, comprehensive and systematic evaluation of its pharmacological mechanisms remains limited. This review systematically analyzes the pharmacological activities of L. rubellus based on in vivo and clinical trial evidence to provide an integrated scientific understanding of its therapeutic potential. A systematic literature search was performed in PubMed, ScienceDirect, Wiley Online Library, Cochrane Library, and Google Scholar for studies published between 2013 and 2022. The review followed PRISMA 2020 guidelines, applying the PICOS framework for eligibility determination. Study quality was assessed using the ARRIVE checklist for in vivo studies and the JADAD scale for clinical trials. Twelve studies met the inclusion criteria, comprising nine in vivo and three clinical trials. Lumbricus rubellus demonstrated multiple pharmacological effects, including fibrinolytic, antibacterial, hepatoprotective, neuroprotective, and anticancer activities. These effects are mainly attributed to proteins such as lumbrokinase and coelomic fluid metabolites that exhibit antithrombotic, anti-inflammatory, and cytoprotective actions. This review highlights strong evidence supporting the diverse pharmacological activities of L. rubellus and its potential as a natural source for developing novel therapeutic agents. Further standardized clinical investigations are required to confirm its efficacy and safety.